Temperature Gradients in the Irradiated Targets During High-Intensity Implantation and Their Influence on Ion-Modified Layer Properties; Surface Modification of Materials by Ion Beams (SMMIB-2019) - Modebadze G. S. Georgy Slavovich; Ryabchikov A. I. Aleksandr Ilyich; Bleykher (Bleicher) G. A. Galina Alekseevna; Ivanova A. I. Anna Ivanovna; Koval T. V. Tamara Vasilievna; Ananin P. S. Petr Semenovich; Shevelev A. E. Aleksey Eduardovich (Ion Beam Processing of Materials. Poster Session, 2019)
Заглавие с экрана